2019
DOI: 10.1177/0047117819852399
|View full text |Cite
|
Sign up to set email alerts
|

A populist grand strategy? Trump and the framing of American decline

Abstract: What is the role of 'populism' in Donald Trump's foreign policy? Defining populism as a framing style that constructs antagonisms around 'the people' and their adversaries, this article explores Trump's rhetoric in relation to his efforts to shift US grand strategy away from its traditional investment in the liberal international order. Based on an approach grounded in the ontological commitments of Critical Discourse Analysis, it examines three interlocking frames: (1) the 'corrupt' elites of the establishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Following Mead (2017), we argue that Jacksonianism is a uniquely American variant of populism, and that Trump has clearly embodied many of the defining traits associated with that tradition: an unabashed military populism, centred on an ethos of pride and respect; a desire to avoid war unless threatened or attacked; clear scepticism of existing international trade and legal agreements; and a general disinterest in issues of human rights, democracy promotion, and nation building abroad (Biegon, 2019; Lacatus, 2021; McDonald, 2018: 412). Most clearly, however, Trump’s claim to be a Jacksonian lies in the views he shares with America’s seventh president: a narrow and often racialised definition of America(ns) and a deep suspicion of those outside of the polis, who are deemed to threaten economic and physical security (Holland, 2020: 219−220).…”
Section: Trump’s Jacksonian Populism and The White (Male) Working Classmentioning
confidence: 96%
See 1 more Smart Citation
“…Following Mead (2017), we argue that Jacksonianism is a uniquely American variant of populism, and that Trump has clearly embodied many of the defining traits associated with that tradition: an unabashed military populism, centred on an ethos of pride and respect; a desire to avoid war unless threatened or attacked; clear scepticism of existing international trade and legal agreements; and a general disinterest in issues of human rights, democracy promotion, and nation building abroad (Biegon, 2019; Lacatus, 2021; McDonald, 2018: 412). Most clearly, however, Trump’s claim to be a Jacksonian lies in the views he shares with America’s seventh president: a narrow and often racialised definition of America(ns) and a deep suspicion of those outside of the polis, who are deemed to threaten economic and physical security (Holland, 2020: 219−220).…”
Section: Trump’s Jacksonian Populism and The White (Male) Working Classmentioning
confidence: 96%
“…As a result, two complementary understandings of Trump have emerged: as a populist leader, mobilising the language of a Jacksonian outsider (e.g. Biegon, 2019; Clarke and Ricketts, 2017; Hamilton, 2017; although contestation is also evident, e.g. Aslam, 2018: 421; Bentley, 2016; Thompson, 2017; Wintour and Borger, 2019).…”
Section: Trump’s Jacksonian Populism and The White (Male) Working Classmentioning
confidence: 99%
“…Although this article conceptualises populism as a form of political rhetoric, it echoes these arguments. That is, there are some even areas within this case study where Trump’s rhetoric has fallen closer in line with his administration’s policies, such as trade (Biegon, 2019: 583; Löfflmann, 2019: 121–122). Furthermore, as populism has a chameleonic nature, we should expect to see an equivalent level of variety in the area of foreign policy.…”
Section: Resultsmentioning
confidence: 94%
“…The relationship between populism and populists in government has been relatively understudied (Verbeek and Zaslove, 2017: 384). Consequently, the connections between populism and foreign policy have also been underexplored, as recent works have attempted to address (Biegon, 2019; Destradi and Plagemann, 2018, 2019; Löfflmann, 2019; Nabers and Stengel, 2019; Wojczewski, 2019). In this sense, this article aims to answer Destradi and Plagemann’s (2018: 299) call for further comparative studies on the relationship in question.…”
Section: Populism and Foreign Policymentioning
confidence: 99%
“…Foreign and security policy experts who analyzed his campaign statements, looking for a coherent underlying philosophy, found none. Early assessments of a possible grand strategy ranged from a new variant of isolationism, 296 to Jacksonian population 297 or illiberal hegemony which, according to Barry Posen, seeks to maintain US economic and military superiority while forsaking democracy promotion and multilateral free trade. 298 In contrast, some authors, for example, Mark Beeson, suggested that Trump took a transactional approach: "Trump believes that his personal qualities, especially in combination with America's economic importance and strategic might, will allow him to negotiate bilateral deals that have eluded other presidents, especially Obama."…”
Section: Donald Trump: Personality Populism and America Firstmentioning
confidence: 99%